2015
DOI: 10.5194/acp-15-1795-2015
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and chlorinated pesticides in background air in central Europe – investigating parameters affecting wet scavenging of polycyclic aromatic hydrocarbons

Abstract: Abstract. Concentrations of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and chlorinated pesticides (CPs) were measured in air and precipitation at a background site in central Europe. ∑ PAH concentrations in air and rainwater ranged from 0.7 to 327.9 ng m−3 and below limit of quantification (< LOQ) to 2.1 × 103 ng L−1. The concentrations of PCBs and CPs in rainwater were < LOQ. ∑ PCB and ∑ CP concentrations in air ranged from < LOQ to 44.6 and < LOQ to 351.7 pg m−3, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…The temperature dependency of θ is more pronounced for FLT, PYR, BAA, and CHR, as evident from data points scattered across the temperature range, particularly for samples from Kosětice; whereas for PHE and BBF the values of θ are close to zero and one, respectively. Median PM 10 concentration was higher at Urla than at Kosětice and Grenoble. In contrast, median f OM values were comparable across all sites, although higher maximum values were found for Kosětice and Grenoble.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The temperature dependency of θ is more pronounced for FLT, PYR, BAA, and CHR, as evident from data points scattered across the temperature range, particularly for samples from Kosětice; whereas for PHE and BBF the values of θ are close to zero and one, respectively. Median PM 10 concentration was higher at Urla than at Kosětice and Grenoble. In contrast, median f OM values were comparable across all sites, although higher maximum values were found for Kosětice and Grenoble.…”
Section: Resultsmentioning
confidence: 93%
“…10,56 Table S4 provides statistics on θ for selected PAHs, as well as ambient temperature, PM 10 concentrations, and the mass mixing ratios of OM, f OM , elemental carbon, f EC , ammonium sulfate, f (NH 4 ) 2 SO 4 , and ammonium chloride, f NH 4 Cl , in PM. Median θ values for semivolatile FLT, PYR, BAA, and CHR were higher for samples from Kosětice than for those from Grenoble and Urla (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The total scavenging ratios (WT; unitless) calculated for the target N/OPAHs were 10 3 -10 4 (Table S4B), which fall 15 within the range suggested for removal of polyaromatic compounds through particle scavenging (Shahpoury et al, 2015). With the exception of 1,4-O2NAP and 9-OFLN, the calculated ratios are consistent with modelled Ө of 0.81-1 (at 273 K) for the target N/OPAHs (Table S4B) in that particle scavenging was the dominant removal mechanism.…”
Section: Modelled Particulate Mass Fractions and Actual Fractions Remmentioning
confidence: 99%
“…It has been shown that the magnitude of particle scavenging is generally higher than gas scavenging for hydrophobic SOCs such as PAHs (Atlas and Giam, 1988;Bidleman, 1988;Shahpoury et al, 2015). In principle, for such substances one could apply Ө as an indicator for predicting the SOC wet particle scavenging -i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation